Length of Vermiform Appendix: A Postmortem Study - Paul, Uttam Kumar; Naushaba, Humaira; Alam, Md Jahangir; Begum, Tahmina; Rahman, Ashfaqur; Akhter, Jesmin (Bangladesh Journal of Anatomy, 2011)
Context: The vermiform appendix is an abdominal organ having variable length and position. It provides immunological function. Vermiform appendix is involved in different disease processes such as appendicitis, carcinoma and diverticulitis. Appendicitis is the most important clinical condition. An appropriate anatomical knowledge about vermiform appendix is important for surgeons, pathologists and other physicians for proper diagnosis and management of appendicitis and carcinoma. Study type : Descriptive type of study. Place and period of the study: Department of Anatomy, Sir Salimullah Medical College, Dhaka from January 2006 to June 2007. Materials and Method: Sixty (60) human postmortem vermiform appendix, age ranging from 0 to 65 years. Fresh samples were collected from the morgue of Sir Salimullah Medical College and Dhaka Medical College, Dhaka. The samples were divided into five (5) different age groups. Result: Length of vermiform appendix decreases gradually with increasing age and was highly significant (P<0.001) when compared between the groups. Key words: Length; Vermiform appendix. DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8140 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 10-12